2005
DOI: 10.1038/sj.ijo.0802888
|View full text |Cite
|
Sign up to set email alerts
|

Low relative resting metabolic rate and body weight gain in adult Caucasian Italians

Abstract: OBJECTIVE: To investigate the relationship between resting metabolic rate (RMR) and subsequent changes in body size and degree of fatness in a group of adult Caucasian Italians. DESIGN: Prospective, longitudinal, observational study. SUBJECTS: In total, 155 subjects (72 males and 83 females, age range: 18-55 y; BMI: 17.5-63.4 kg/m 2 ) were evaluated. In total, 43 (26 m and 17 f; BMI: 28.971.1 kg/m 2 , mean7s.e.m.) of them were reassessed 10-12 y later. MEASUREMENTS: Anthropometric and body composition (bioimpe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
50
1
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(60 citation statements)
references
References 21 publications
5
50
1
1
Order By: Relevance
“…Most studies enrolled obese participants (mean BMI: 32-36) (3)(4)(5), and some of studies included relatively small numbers of subjects (6) or had shorter durations of follow-up (3,4). The percentage of subjects in whom we were able to collect follow-up weight data was comparable with that in other studies (3,5) and much greater than the 30% follow-up reported in a study of Italian adults (6). One study of lean Nigerians showed that higher resting energy expenditures (REEs) were positively associated with weight gain (8), but the REE was not measured under as carefully controlled conditions, and body composition was measured by bioelectrical impedance, either of which could have affected the results.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Most studies enrolled obese participants (mean BMI: 32-36) (3)(4)(5), and some of studies included relatively small numbers of subjects (6) or had shorter durations of follow-up (3,4). The percentage of subjects in whom we were able to collect follow-up weight data was comparable with that in other studies (3,5) and much greater than the 30% follow-up reported in a study of Italian adults (6). One study of lean Nigerians showed that higher resting energy expenditures (REEs) were positively associated with weight gain (8), but the REE was not measured under as carefully controlled conditions, and body composition was measured by bioelectrical impedance, either of which could have affected the results.…”
Section: Discussionsupporting
confidence: 64%
“…The retrospective cohort study design meant that we could not collect data from people who moved away. However, our follow-up rates were comparable with or better than those of studies that reported significant associations between BMR and subsequent weight gain (3,5,6). Because it was not possible to collect comprehensive information regarding the diet and activity habits for the w9 y after the original studies, we cannot know why adults with low BMRs gained no more weight than did adults with high BMRs.…”
Section: Discussioncontrasting
confidence: 45%
See 1 more Smart Citation
“…7 Increased sedentary behaviour is an important factor in the development of human obesity. 10 Whilst low-resting energy expenditure may contribute to obesity, 11,12 recent research has indicated it has minimal impact on weight gain 13,14 and activity-related energy expenditure may be much more important. 15 It has been reported that low physical activity accounted for 77% of weight gain over a year in one prospective study 16 and inactivity is a major determinant of increased adiposity during overfeeding.…”
Section: Introductionmentioning
confidence: 99%
“…41,42 It is well documented that increased weight gain in some obese mouse models is related to a reduction in RMR and core body temperature. 43,44 Indeed, there have been several case reports of risperidone-and olanzapine-induced hypothermia in patients; [45][46][47][48][49][50] however, these case studies do not indicate the risk of weight gain associated with the hypothermia.…”
Section: Discussionmentioning
confidence: 99%